(untitled) (Global Journal of Management and Business Research, 2016)
This paper advocates the extension of the resource based view (RBV) by proposing a new theory to understand the actual creation process of sustainable competitive advantage using a services firm in the motor industry in Kenya as a case, by integrating the activity-based view (ABV) with the RBV, through activity drivers, to generate a new theory: Activity-resourcebased view (ARBV). A qualitative case study of a consistently high performing firm in the motor services industry in Kenya was used to determine if the ARBV assists in creating a sustainable competitive advantage. The results from the in depth semi-structured qualitative case study shows that a firm in a motor service industry that adopts the new theory, ARBV, will generate and sustain a competitive advantage for itself.